Mercury Exposure and Risk of Type 2 Diabetes: A Systematic Review and Meta-Analysis. (2nd September 2022) - Ghorbani Nejad, Behnam; Raeisi, Tahereh; Janmohammadi, Parisa; Mehravar, Fatemeh; Zarei, Mahtab; Dehghani, Azadeh; Bahrampour, Niki; Darijani, Mohammad Hosein; Ahmadipour, Fatemeh; Mohajeri, Mohammad; Alizadeh, Shahab
Abstract : Background and Aim . Previous studies have indicated that exposure to mercury (Hg) may be associated with odds of type 2 diabetes mellitus (T2DM). However, the available evidence is contradictory. This meta-analysis aimed to examine the relationship of Hg with the risk of T2DM. Methods . Scopus and PubMed databases were systematically searched from their inception to November 2021 to obtain pertinent studies. Standardized mean differences (SMDs) with corresponding 95% confidence intervals (CIs) were calculated to evaluate the difference in Hg levels between people with and without T2DM. The association of the Hg exposure with T2DM was assessed using a random-effects model by pooling the odds ratios (ORs) and 95% CIs. Results . A total of 17 studies, with 42, 917 participants, aged ≥18 years, were analyzed. Overall, Hg levels were significantly higher in T2DM patients compared with non-T2DM controls (SMD = 1.07; 95%CI = 0.59 to 1.55, P ≤ 0.001 ), with significant heterogeneity across studies (I 2  = 96.1%; P = ≤ 0.001 ). No significant association was found between Hg exposure and risk of T2DM in the overall analysis and subgroup analysis based on the source of sample and study design. However, higher exposure to Hg was related to reduced risk of T2DM in men (OR = 0.71; 95%CI = 0.57 to 0.88), but not in women. No significant evidence for publication bias was detected. Conclusions . Although the Hg level in T2DM is significantly higher than that of nondiabetics, there was no association between Hg exposure and the overall risk of T2DM. Nevertheless, our study shows that higher exposure to Hg might reduce the risk of T2DM in men.